Oxygen Deprivation Implicated in Rapid Coral Mortality Under Acute Heating Events - Max S. Dhillon; Shannon G. Klein; Dilip Kr. Maity; Anieka J. Parry; Alessandro Moret; Walter Dellisanti; Abhijit Kr. Kushwaha; Sandip Dighe; Cesar O. Pacherres; Michael Kühl; Tadd Truscott; Carlos M. Duarte; et al. (Global Change Biology, 2026)
While coral bleaching is a well‐known consequence of marine heatwaves, rapid coral mortality via tissue disintegration is an understudied threat; one that precludes any chance of recovery. We show that tissue disintegration can occur within hours to days of acute heat stress, marking a critical survival threshold. Micro‐scale oxygen measurements indicate rapid deoxygenation of coral tissue immediately preceding tissue disintegration. We hypothesise that the simultaneous impairment of photosynthetic oxygen supply and increased holobiont oxygen demand overwhelm a coral's ability to maintain basal metabolic functions. Theoretical oxygen flux calculations support this, suggesting that passive diffusion alone is insufficient to meet metabolic demand under these conditions. These findings highlight intrinsic oxygen deprivation as a potential mechanism for rapid coral mortality and suggest a new, more immediate thermal limit for corals, urging further investigation into the thermal conditions and mechanisms that trigger this response.